Seasonality Fingerprint on Global Trading of Food-commodities. A Data-mining Approach - Stefania Quaini; Sebastiano Saccani; Sergio Vergalli; Luigi Assom; Marco Beria; Alessandro Codello; Maurizio Monaco; Riccardo Sabatini (Fondazione Eni Enrico Mattei (FEEM), 2020)
We analyze the United Nations commodities trade database (UN comtrade), comprised of international commodities exchanges in volume and price with monthly resolution. We introduce a trade impact index to quantify the impact, in terms of distance travelled, of importing a specific food raw commodity in a specific period of the year and in a specific country of the world. This index captures the seasonal exchange of raw commodities in an insightful and concise manner.
Keywords: F18; Q17; C8; C43; 330; Trade; Food Commodities; Resource Access and Availability; Index; Fingerprint; Data Mining